Reproductive outcomes in men with karyotype abnormalities: Case report and review of the literature - Kohn, Taylor P.; Clavijo, Raul; Ramasamy, Ranjith; Hakky, Tariq; Candrashekar, Aravind; Lamb, Dolores J.; Lipshultz, Larry I. (Canadian Urological Association Journal, 2015)
Reciprocal translocations of autosomal chromosomes are present in about 1/625 men, yet often there are no symptoms except primary infertility. Abnormal segregation during meiosis often produces sperm and subsequent embryos with unbalanced translocations that often ultimately result in spontaneous abortions. We report on a 37-year-old man and his 39-year-old wife who complained of primary infertility. Previous in vitro fertilization (IVF) had resulted in pregnancy, but two spontaneous abortions. Upon chromosomal testing, the man was diagnosed with a reciprocal translocation and his wife was diagnosed with mosaic Turner’s syndrome. Through testicular sperm extraction (TESE) and IVF with preimplantation genetic screening (PGS), they succeeded in having two healthy children. Since men with different karyotype abnormalities can have male infertility, we reviewed the literature and summarized the reproductive outcomes for men with both autosome and sex chromosomal karyotype abnormalities.